Human CASPR2 Antibodies Reversibly Alter Memory and the CASPR2 Protein Complex. Issue 6 (22nd March 2022) - Joubert, Bastien; Petit‐Pedrol, Mar; Planagumà, Jesús; Mannara, Francesco; Radosevic, Marija; Marsal, Maria; Maudes, Estibaliz; García‐Serra, Anna; Aguilar, Esther; Andrés‐Bilbé, Alba; Gasull, Xavier; Loza‐Alvarez, Pablo; et al.
Abstract : Objective: The encephalitis associated with antibodies against contactin‐associated proteinlike 2 (CASPR2) is presumably antibody‐mediated, but the antibody effects and whether they cause behavioral alterations are not well known. Here, we used a mouse model of patients' immunoglobulin G (IgG) transfer and super‐resolution microscopy to demonstrate the antibody pathogenicity. Methods: IgG from patients with anti‐CASPR2 encephalitis or healthy controls was infused into the cerebroventricular system of mice. The levels and colocalization of CASPR2 with transient axonal glycoprotein 1 (TAG1) were determined with stimulated emission depletion microscopy (40–70μm lateral resolution). Hippocampal clusters of Kv1.1 voltage‐gated potassium channels (VGKCs) and GluA1‐containing α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors (AMPARs) were quantified with confocal microscopy. Behavioral alterations were assessed with standard behavioral paradigms. Cultured neurons were used to determine the levels of intracellular CASPR2 and TAG1 after exposure to patients' IgG. Results: Infusion of patients' IgG, but not controls' IgG, caused memory impairment along with hippocampal reduction of surface CASPR2 clusters and decreased CASPR2/TAG1 colocalization. In cultured neurons, patients' IgG led to an increase of intracellular CASPR2 without affecting TAG1, suggesting selective CASPR2 internalization. Additionally, mice infused with patients' IgG showed decreased levels of Kv1.1 and GluA1 (two CASPR2‐regulated proteins). All these alterations and the memory deficit reverted to normal after removing patients' IgG. Interpretation: IgG from patients with anti‐CASPR2 encephalitis causes reversible memory impairment, inhibits the interaction of CASPR2/TAG1, and decreases the levels of CASPR2 and related proteins (VGKC, AMPAR). These findings fulfill the postulates of antibody‐mediated disease and provide a biological basis for antibody‐removing treatment approaches. ANN NEUROL 2022;91:801–813